Protection of Patent Holders’ Rights in Indonesia: Between Theories and Practices - Uche Nnawulezi; Eva Diah Pitaloka; Indah Fitri Cahyani; Julian Naridha Putri (Journal of Private and Commercial Law, 2023)
Intellectual property constitutes a vital aspect of rights, with patents being a crucial element of intellectual property rights (IPRs). A patent grants an inventor the exclusive right, recognized by the state, to their technological invention for a specified duration, either for personal implementation or through agreements with others. Patents hold great strategic and economic significance for their owners, offering legal protection under national law. This protection serves to incentivize creators to advance quantity and quality, fostering prosperity and a healthy business environment within society. Indonesia, as an active participant in international trade, ratified the establishment of the WTO on November 2, 1994, encompassing the TRIPs agreement, which sets international standards for intellectual property rights. Presently, the safeguarding of patent rights in Indonesia is governed by Law No. 13 of 2016, encompassing both patents and simple patents. This legal framework underscores the government’s commitment to enforcing intellectual property rights protection. The study adopts a qualitative approach, aiming to explore and optimize the legal protection of patent holders in Indonesia.